Diversity and Distribution of Fungi in the Marine Sediments of Zhanjiang Bay, China - Menghan Gao; Bihong Liu; Jianming Li; Yunyan Deng; Yulei Zhang; Ning Zhang; Feng Li; Changling Li; Xianghu Huang; Zhangxi Hu (Journal of Fungi)
Fungi are one of the major components of the eukaryotic microbial community in marine ecosystems, playing a significant role in organic matter cycling and food web dynamics. However, the diversity and roles of fungi in marine sediments remain poorly documented. To elucidate the diversity and spatial distribution of fungal communities in the marine sediments of an estuary–coast continuum across three distinct salinity regions in Zhanjiang Bay, China, the variations in fungal diversity, abundance, community structure, and distribution in the sediments were investigated through the application of high-throughput amplicon sequencing using the internal transcribed spacer (ITS) primers. Additionally, the FUNGuild database was employed to assess the potential functional traits of fungi. A total of 1242 ASV sequences, affiliated to 144 genera and five phyla, were identified. Ascomycota (68.97%) and Basidiomycota (6.41%) were the dominant fungal groups, together accounting for 75.38% of the total relative abundance of the fungal community. Significant differences were observed in the α-diversity indices (Shannon index and richness) and β-diversity of fungal communities across the three distinct salinity regions. The fungal molecular network exhibited primarily positive species interactions, with notable structural differences across salinity gradients. The low-salinity group had a large network with high modularity; the medium-salinity group a small, simple network with high centralization, and the high-salinity group a compact, moderately complex network. Symbiotrophs, saprotrophs, and pathotrophs, being the three trophic types with the highest proportions, were estimated based on ITS. A redundancy analysis (RDA) indicated that salinity was the primary factor influencing the distribution of Ascomycota communities, while the distributions of Basidiomycota, Chytridiomycota, Mucoromycota, and Rozellomycota were more strongly affected by environmental factors such as chlorophyll a, chemical oxygen demand (COD), pH, and temperature. Our work provides new scientific data on the diversity, composition, and distribution of fungal communities in Zhanjiang Bay, which helps to understand the biodiversity of fungi in the estuary–coast ecosystems.